A Review of Environmental Screening on Strategic Formulation in Health Care Sector - KasihPuji Utami; Nur Wening (Institute of Medico-legal Publications Pvt Ltd, 2021)
This paper is a literature review that discusses the screening of the business environment in strategyformulation. The purpose of the review is to explore and connecting theories from various research. Thispaper identified 22 articles with related topics published the last decade. The results of this study show thatscreening of the external environment that is important to do is the general environment (politics, economy,socio-culture, technology, demography, and epidemiology) which plays a role of 66.66%. While internalenvironmental analysis that is important to do is resources (finance, physical, technology, human resources,innovation and reputation) and value chain management (infrastructure, HRM, technology development,purchasing, inbound logistics, operations, outbound logistics, sales and marketing, and services) playeda role of 33.33%.Based on a summary related to research on internal and external factors that have beencarried out in health facilities, it is known that industrial environmental factors and environmental factors ofcompetitors are still minimally studied so that they can become opportunities for future research.